Common Variants of IL6, LEPR, and PBEF1 Are Associated With Obesity in Indian Children - Tabassum, Rubina (American Diabetes Association, 2012)
The increasing prevalence of obesity in urban Indian children is indicative of an impending crisis of metabolic disorders. Although perturbations in the secretion of adipokines and inflammatory molecules in childhood obesity are well documented, the contribution of common variants of genes encoding them is not well investigated. We assessed the association of 125 common variants from 21 genes, encoding adipocytokines and inflammatory markers in 1,325 urban Indian children (862 normal weight [NW group] and 463 overweight/obese [OW/OB group]) and replicated top loci in 1,843 Indian children (1,399 NW children and 444 OW/OB children). Variants of four genes (PBEF1 [rs3801266] [P = 4.5 × 10(−4)], IL6 [rs2069845] [P = 8.7 × 10(−4)], LEPR [rs1137100] [P = 1.8 × 10(−3)], and IL6R [rs7514452] [P = 2.1 × 10(−3)]) were top signals in the discovery sample. Associations of rs2069845, rs1137100, and rs3801266 were replicated (P = 7.9 × 10(−4), 8.3 × 10(−3), and 0.036, respectively) and corroborated in meta-analysis (P = 2.3 × 10(−6), 3.9 × 10(−5), and 4.3 × 10(−4), respectively) that remained significant after multiple testing corrections. These variants also were associated with quantitative measures of adiposity (weight, BMI, and waist and hip circumferences). Allele dosage analysis of rs2069845, rs1137100, and rs3801266 revealed that children with five to six risk alleles had an approximately four times increased risk of obesity than children with less than two risk alleles (P = 1.2 × 10(−7)). In conclusion, our results demonstrate the association of the common variants of IL6, LEPR, and PBEF1 with obesity in Indian children.